Makna Kepemimpinan Adaptif dalam Organisasi Modern: Studi Fenomenologi terhadap Transformasi Budaya Kerja di Era Disrupsi - Agus Salen; Romansyah Sahabuddin; Chalid Imran Musa; Thamrin Tahir; Agung Widhi Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to understand the meaning of adaptive leadership in modern organizations facing transformations in work culture during the era of disruption. Using a phenomenological qualitative approach within the social constructivist paradigm, this research explores the lived experiences of leaders in interpreting change, uncertainty, and human values amid digitalization and organizational complexity. Data were collected through in-depth interviews and non-participant observation involving eight leaders from various industrial sectors in Indonesia and were analyzed using Colaizzi’s phenomenological analysis technique. The findings reveal that adaptive leadership is understood as a reflective and social process rooted in value awareness, empathy, and collective learning capacity. Adaptive leaders not only direct change but also facilitate learning and build trust through open communication and collaborative work cultures. Adaptive values such as flexibility, empathy, and moral reflection are key to shaping inclusive and sustainable organizational cultural transformation. Theoretically, this study extends the discourse on adaptive leadership within phenomenological and social contexts, while practically emphasizing the importance of value-based reflective leadership in navigating disruptive change.